VD_FINDINFO Décision / 2012 / 919 vom 1. November 2012 - VD Tribunal cantonal (2012)
MESURE DE SÛRETÉDROIT PÉNAL, MOTIF DE DÉTENTION, PROPORTIONNALITÉ | 212 al. 3 CPP (CH), 221 al. 1 let. a CPP (CH), 229 al. 1 CPP (CH), 229 al. 3 let. b CPP (CH), 229 CPP (CH), 237 CPP (CH)